Probing Nanometer-Thick Polyelectrolyte Layers Adsorbed on Oppositely Charged Particles by Dynamic Light Scattering - Hierrezuelo-Osorio, José Manuel; Szilagyi, Istvan; Vaccaro, Andrea; Borkovec, Michal (ACS, 2010)
The thickness of adsorbed polyelectrolyte layers on oppositely charged particles can be measured by dynamic light scattering (DLS) with a precision of fractions of a nanometer. However, such data can be only reliably obtained when effects of particle aggregation are carefully eliminated by working at low particle number concentrations. In order to achieve a sufficient light scattering intensity at the same time, the size of colloidal particles must be chosen relatively large. We find that such measurements are best carried out with latex particles in the range of diameters of 150-300 nm. The precision of the measurement can be further enhanced with multiangle DLS. The thickness of adsorbed polyelectrolyte layers on oppositely charged particles is normally below 10 nm. At low ionic strengths, a typical thickness is merely 1-2 nm, while at higher ionic strengths one observes thicknesses between 6 and 9 nm. The transition between these two regimes occurs at ionic strengths 0.01-0.05 M. These observations were made with various highly charged cationic and anionic polyelectrolytes and can be considered as quite generic.
https://v2.sherpa.ac.uk/id/publication/7790
Keywords: Hidrodinámica; Hydrodynamics; Layers; Thickness